Analisis Pengembangan Wisata Kuliner Kota Medan - Hasibuan, Vera Yunita; Yusrizal; Jannah, Nurul (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
This study aims to determine the development strategy for the culinary tourism business in Medan City. This research method is field research with a qualitative-descriptive approach. research that emphasizes aspects of in-depth understanding of a problem rather than looking at problems for generalization research. This research method uses in-depth analysis techniques. Based on the results of the research that has been done, the strategy for developing culinary tourism to prosper the economy in Medan City is by using a SWOT analysis, namely by using the SO strategy, WO strategy, ST strategy and WT strategy. The results of this analysis are maintaining the taste and uniqueness as well as product quality, increasing partnerships with the government, improving better tourist destinations. The author's suggestions are to improve the facilities and quality of human resources, innovate, involve food bloggers or food vloggers for promotions, and organize events to make them more widely known.